Equity in higher education and graduate labour market outcomes in Australia - Li, I.; Mahuteau, S.; Dockery, Alfred Michael; Junankar, P. (Routledge, 2017)
© 2017 Association for Tertiary Education Management and the LH Martin Institute for Tertiary Education Leadership and Management. The rate of higher education participation in Australia has increased over the past decade for individuals from disadvantaged backgrounds. This study contributes to the knowledge on the outcomes of disadvantaged individuals who complete higher education by looking at the labour market outcomes of university graduates from equity groups. The number of Indigenous graduates and graduates with disabilities was found to be very low, suggesting that more needs to be done to improve higher education completion for these two groups. The labour market outcomes for other equity groups are mixed, with those from low socio-economic status backgrounds and regional and remote Australia performing well in the labour market, while graduates from non-English-speaking backgrounds and female graduates in science, technology, engineering and mathematics fields experience substantial disadvantage in the labour market. The findings suggest that selection processes prior to the graduates’ entry into the labour market are important.